TARI KESUME GAYO PADA MASYARAKAT GAYO KABUPATEN ACEH TENGAH TINJAUAN TERHADAP BENTUK - WAHYU DESIANA SYAHZUAR (Gesture: Jurnal Seni Tari, 2013)
Dance Kesume Gayo In Aceh Tengah Regency Gayo Community Review Of The Forms. Thesis The purpose of this research is to discuss about the history and form of the dance Kesume Gayo. The theoretical basis is used to discuss the research is using the theories related to topics such as the origins of the theory, and the theory of forms. The research carried out for 2 months i.e. may 2014 until July 2014. The location of the research done in the area of Central Aceh Regency of Takengon. The methods used to discuss the form of the dance Kesume qualitative descriptive method using Gayo. The population in this research as well as a sample of interviewees, officials of the Department of culture of Central Aceh Regency, and artists who know about the shape of the dance Kesume Gayo. Data collection techniques include the study of librarianship, observation, interview and documentation. Based on the results of the research done then it can deduce the outline that the origins of the dance Kesume Gayo in Aceh Tengah Regency Gayo Society, created by Alm.A.R. Moese and YusRetno in 1961 and was performed at the Court of the State in the 1970s and 1980s. In addition ever performed on the PKA in 1988. Creation Dance Kesume Gayo inspired from bersawah's activities until the rice harvest. As for the arrangement and form of the dance Kesume Gayo refers to the relationship of interplay between the elements that are used namely motion, themes, musical accompaniment, tata clothing, tat arias, property and staging areas. As for the form of the dance Kesume Gayo Keywords : Dance, Dance Structure